1978
DOI: 10.1136/jcp.31.9.840
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pathogenic yeasts and humoral antibodies to candida in diabetic patients.

Abstract: SUMMARY The prevalence of oral yeasts and humoral precipitating antibodies to candida was estimated in 204 unselected diabetic patients (172 outpatients and 32 inpatients). Yeasts, mainly Candida albicans, were isolated from the mouths of 41 % of the outpatients and precipitins were found in 17-5 % although none of the patients had clinically overt candidiasis. The extent of oral yeast colonisation and incidence of antibodies was not related to their antidiabetic treatment or to the duration of their diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
3

Year Published

1982
1982
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 22 publications
4
27
3
Order By: Relevance
“…In this study only 54 % of the isolates were C. albicans (Table 2); this figure includes the proportion that was not identified by API 20C Aux as C. albicans but found to be so by conventional methods. These results are similar to studies which found 60 % of isolates from diabetics to be C. albicans [3,16]. This emphasizes the need for accurate identification as patients with diabetes are more likely to carry and to have disease due to species other than C. albicans [18] which might not be sensitive to routinely prescribed oral antifungal agents [19].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study only 54 % of the isolates were C. albicans (Table 2); this figure includes the proportion that was not identified by API 20C Aux as C. albicans but found to be so by conventional methods. These results are similar to studies which found 60 % of isolates from diabetics to be C. albicans [3,16]. This emphasizes the need for accurate identification as patients with diabetes are more likely to carry and to have disease due to species other than C. albicans [18] which might not be sensitive to routinely prescribed oral antifungal agents [19].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, 66 % of the diabetics were carriers of yeasts by the oral rinse technique, a figure slightly higher than those reported in previous studies of diabetics (41-62%) [2,3,5,6,16].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The increased candidal colonization in diabetic patients could be attributed to the promotion of the binding of Candida to epithelial cells and reduction of tissue resistance against infection. Likewise, salivary glucose and pH levels are correlated with the increased carriage rate of Candida in diabetic patients [16][17][18] . In the present study, diabetic patients aged 40-60 years old with high salivary glucose, low salivary pH, history of xerostomia, and low oral hygiene showed more than 50 colonies of Candida in their mouth.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is accepted that high salivary glucose levels among diabetics favour the growth of yeasts. 17,37 However, some investigators have not been able to show a relationship between glycaemic control and oral carriage. 38,39 It seems that defects in Candida-cidal activity of neutrophils, particularly in the presence of glucose may promote oral carriage of Candida among diabetics.…”
Section: Diabetes and Oral Candidiasismentioning
confidence: 99%